Model Pengelolaan Pendidikan Multikulkural di Pondok Pesantren Tradisional dan Modern - Arief Efendi (El-Idare, 2017)
This study aimed to describe the management model of multicultural education in traditional and modern boarding school in maintaining harmony heterogeneity students. This type of research is a qualitative study using a naturalistic approach. Subjects in this study were caregivers, teachers, traditional and modern pesantren students at two boarding schools are boarding Sunan Pandanaran Yogyakarta and modern cottage Al-barakah Nganjuk East Java. namely data collection techniques interviews, observations and document research. The results of this study: first, the model of multicultural education in the form of a traditional boarding school, namely a) the use of Indonesian as the unifying language students in learning activities and daily activities; b) intermingling of students as a vehicle to learn to live in diversity, to build mutual trust, mutual understanding  and mutual respec; c) the appreciation of multicultural education in a variety of activities: the use of batik regional origin of students; activities miss the archipelago and fashion show